Indonesia Constitutional Court Constitutional Interpretation Methodology (2003-2008) - Siregar, Fritz Edwadr (Constitutional Review, 2015)
Nine Indonesian Constitutional Justices have the authority to annul a law drafted by 550 Parliament members and the President. The Constitutional Â Court of the Republic of Indonesia (âthe Courtâ), particularly in deciding cases Â of judicial review, has the capability to declare words, sentences, paragraphs, articles or the law unconstitutional. Consequently, it is essential for the Court Â to take into account legal arguments. The fundamental element of these legal arguments is constitutional interpretation, which serves as a parameter in determining constitutionality of the laws. However, in exercising its authority, the Court needs to interpret the Constitution as a Â basis Â for deciding Â a case. Â The standards for determining the constitutionality of a law must be the text of the Constitution, not what the judges would prefer the Constitution to mean. Constitutional supremacy necessarily assumes that a superior rule is what the Constitution says it is, not what the judges prefer it to be. [Craig R. Ducat: E3]. The Court period 2003â2008 were the Courtâs the formative years, and as such are important to understand the methodology and interpretative approaches adopted by the Court. Many observers of the Courtâs early decisions are still unsure of the overarching approach and methodology adopted by the Court. Thus, there is a need Â for a close analysis and criticism of Â the Courtâs early decisions Â  to determine which methods and approaches it has adopted and whether these are appropriate in the Indonesian context. The Court has openly referred to the experiences of foreign jurisdiction in constitutional law, and therefore it would be appropriate to analyze the courtâs decisions in a broader comparative context of constitutional interpretative approaches from around the Â world.